2015
DOI: 10.4172/2155-952x.1000171
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Effect of Coated Leather Based on Silver Nanoparticles and Nanocomposites: Synthesis, Characterisation and Microbiological Evaluation

Abstract: This paper describes the assessment of the antimicrobial effect of leathers employed for footwear production, which were obtained by different tanning techniques and treated with silver nanoparticles emulsions synthesised from different reducing agents (sodium borohydride, gelatine/glucose and Aloe vera extract), as well as the assessment of the silica nancomposites obtained from said nanoparticles. After the characterisation of silver nanoparticles and nanocomposites, the emulsions were applied onto different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 23 publications
0
2
0
3
Order By: Relevance
“…Beberapa penelitian penggunaan nanopartikel perak pada kulit telah dilakukan diantaranya penggunaan Nano-Ag-TiO2 untuk pelapisan (coating) pada kulit lapis (Kayguzuz et al, 2016) dan penggunaan nanopartikel perak untuk insock, lining dan upper material (Lopez et al, 2015) dan kulit berbulu (Perumalraj, 2012). Karakterisasi dan uji performance material kulit menggunakan nano partikel perak dilakukan oleh (Lkhagvajav et al, 2015).…”
Section: Pendahuluanunclassified
See 2 more Smart Citations
“…Beberapa penelitian penggunaan nanopartikel perak pada kulit telah dilakukan diantaranya penggunaan Nano-Ag-TiO2 untuk pelapisan (coating) pada kulit lapis (Kayguzuz et al, 2016) dan penggunaan nanopartikel perak untuk insock, lining dan upper material (Lopez et al, 2015) dan kulit berbulu (Perumalraj, 2012). Karakterisasi dan uji performance material kulit menggunakan nano partikel perak dilakukan oleh (Lkhagvajav et al, 2015).…”
Section: Pendahuluanunclassified
“…Karakterisasi nano partikel Ag menggunakan spektroskopi dan studi keamanan Nano partikel Ag sebagai antibakteri pada kulit telah dilakukan oleh (Sportelli et al, 2017). Lopez et al, (2015) melakukan penelitian tentang Pengaruh coating nanopartikel perak sebagai antibakteri dari sintesis, karakterisasi dan evaluasi mikrobiologi. Studi tentang peningkatan sifat permukaan kulit yang dicoating dengan nanopartikel perak (Ag NPs) telah dilakukan oleh Elsayed et al, (2021).…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Therapeutic applications include catheters [11] and wound dressings [12]. Several studies have reported the application of AgNPs to leathers as colloidal solutions and emulsions [13,14] and through microencapsulation [15].…”
Section: Introductionmentioning
confidence: 99%
“…However, very few reports on the toxicity of Ag-NPs are available, which show different degrees of in vitro cytotoxicity [7,8]. Several studies have reported the application of Ag-NPs in leathers, as colloidal solutions and emulsions of Ag-NPs [9,10], via Ag-NPs microencapsulation [11], and Ag-NPs synthesis using natural polymers such pine resin or gum [12].…”
Section: Introductionmentioning
confidence: 99%